What can we learn from surveys on the importance of software development productivity factors? - Jørgensen, Magne (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2023)
A proper interpretation of survey results on the importance of software development productivity factors requires an understanding of what the responses reflect. To find out more about this, we conducted a survey with 79 experienced software professionals. The strongest connection found was between the high perceived importance of a productivity factor and how frequently the respondents had experienced that a low performance on that factor had caused productivity problems. We argue that it is challenging to interpret survey-based results on the importance of productivity factors. Instead of conducting more surveys on the importance of such factors, we recommend asking directly about previous experiences related to productivity factors and including contextual information that enables proper interpretation of the responses.